Facile Synthesis of NaYF4:Yb Up-Conversion Nanoparticles Modified with Photosensitizer and Targeting Antibody for In Vitro Photodynamic Therapy of Hepatocellular Carcinoma. (8th March 2022) - Ding, Jingyi; Jin, Yan; Zhu, Fengqi; Zhu, Cunle; Peng, Jiang; Su, Tiantian; Cai, Jinzhen
Abstract : Rare Earth up-conversion nanoparticles NaYF4:20%Yb, 2%Er@PEI (UCNPs) were generated via a one-step hydrothermal technique at relatively reduced temperatures. Photosensitizer Ce6 and anti-EpCAM, a highly expressed monoclonal antibody in cancer stem cells of hepatocellular carcinoma, were linked to UCNP surfaces via the formation of amide linkage between carboxyl from Ce6 or anti-EpCAM and abundant amino from PEI, leading to the formation of Ps-Ce6 and anti-EpCAM-UCNPs-Ce6 nanoparticles. The synthesized nanoparticles characterized by XRD, TEM, and IR, and their zeta potential, ROS generation ability, Ce6 loading rate, and up-conversion fluorescence properties were investigated. It has been revealed that all the products were uniformly dispersed nanoparticles (25–32 nm), which crystallized primarily as hexagonal structures, and their up-conversion fluorescence spectra were similar to that of NaYF4:20%Yb, 2%Er. The Ce6 loading rate in the anti-EpCAM-UCNPs-Ce6 nanoparticles was about 2.9%, thereby resulting in good ROS generation ability. For anti-EpCAM-UCNPs-Ce6, the biosafety, targeting effect, and PDT effect exposed under near-infrared (NIR) laser (980 nm) were evaluated using human liver cancer cells (BEL-7404). The results showed that it has good biocompatibility and biosafety as well as high targeting and PDT treatment efficiencies, which renders it a potential experimental material for the near-infrared PDT study.